Navorsing in die filosofiese wetenskappe, met verwysing na die Fundamentele opvoedkunde - Walt, J. L. van der (Koers, 1988)
It is widely recognized among scientists that quantitative research methods are applicable in cases where the field of inquiry and the problem to be solved require such research. History proves however that such strict quantitative research methods have in the past also found their way into the humanities, mainly because of the efforts of positivists, instrumentalists and pragmatists. In many cases, though, it can be proved that the one sided application of these methods in the humanities has not been suitable, since there are too many anthropological variables to be controlled and too many (including statistical) suppositions to be formulated at the outset. Although the value of these methods in the humanities in cases where their application is justifiable cannot be denied, there has lately been a strong thrust for the advancement of qualitative research in the human sciences, including education. Qualitative re search methods have in fact through the centuries consistently featured prominently in the philosophical disciplines like philosophy of education, although there are traces of efforts to apply quantitative methods in these disciplines too. Through the ages, from the maieutic method of Socrates to the contemporary method of conceptual analysis, philosophers have always endeavoured to outline their methods of research, methods which have always been mostly qualitative by nature.